1987
DOI: 10.1177/030098588702400510
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic and Electron Microscopic Studies on the Acute Toxicity of Ochratoxin A in Rats

Abstract: Ochratoxin A was given by gavage to male rats. Moribund and dead animals were necropsied, and the surviving rats, including the controls, were killed 48 hours after dosing. Many of the principal rats were moribund, or began dying, within 12 to 24 hours after dosing. Lesions suggestive of disseminated intravascular coagulation were seen by light microscopy as early as 12 hours after dosing; fibrin deposits were in the spleen, brain choroid plexus, glomerular capillaries, liver, and heart. Renal tubular nephrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0
1

Year Published

1993
1993
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 15 publications
4
19
0
1
Order By: Relevance
“…Similar observations have been made by other authors in rats and mice (Fuchs and Hult 1992, Fuchs et al 1988, Roth et al 1988. The reabsorption of OTA by the kidney has also been proposed to facilitate the residual persistence of the toxin and hence the observed renal toxicity in rodents (Albassam et al 1987, Stein et al 1985. In vivo metabolism of OTA in a number of species including rodents (Størmer et al 1981) and ruminants (Pitout 1969) has been shown to yield predominantly the non-toxic congener ochratoxin-a (OT-a), i.e.…”
Section: Kinetic Studiessupporting
confidence: 79%
“…Similar observations have been made by other authors in rats and mice (Fuchs and Hult 1992, Fuchs et al 1988, Roth et al 1988. The reabsorption of OTA by the kidney has also been proposed to facilitate the residual persistence of the toxin and hence the observed renal toxicity in rodents (Albassam et al 1987, Stein et al 1985. In vivo metabolism of OTA in a number of species including rodents (Størmer et al 1981) and ruminants (Pitout 1969) has been shown to yield predominantly the non-toxic congener ochratoxin-a (OT-a), i.e.…”
Section: Kinetic Studiessupporting
confidence: 79%
“…58,74,75 The reabsorption of OTA by the kidney has also been proposed to facilitate the residual persistence of the toxin and hence the renal toxicity in rodents. 76,77 In vivo metabolism of OTA in a number of species including rodents 78 and ruminants 79 has been shown to predominantly yield the nontoxic congener ochratoxin-α, that is, the isocumarin moiety lacking the phenylalanine group (Figure 1). This metabolic peptide bond cleavage appears to be a function of the intestinal tract, as little conversion of the parent compound has been observed in either kidney or liver.…”
Section: Protein Binding and Kineticsmentioning
confidence: 99%
“…However, other toxic eOE ects observed include cardiac and hepatic histological abnormalities, aberration of coagulation factors in the rat, accompanied by haemorrhage and thrombosis in the spleen, brain, liver, kidney and heart (Albassam et al 1987), lesions of the gastrointestinal tract and lymphoid tissues in the hamster (Hagelberg et al 1989), myelotoxicity in mice (Boorman et al 1984, MuÈ ller et al 1995, and intestinal fragility and kidney lesions in chickens (Elling et al 1975). Prior et al (1980) noted decreased feed intake in chickens exposed to feed contaminated with 0.5 ppm OTA.…”
Section: Summary Of the Toxic Eoe Ects Of Ota And Citrininmentioning
confidence: 99%